(untitled) (Research, Society and Development, 2021)
The present manuscript aims to analyze the impact of artificial intelligence in the construction of Law as a decision rule. The dialogue between artificial intelligence and law, in this way, it is essential to investigate the definition of artificial intelligence, as well as conducting a thorough investigation of the decision-making process, using Friedrich Müller as a reference. In this perspective, this article, through explanatory research, of a qualitative nature, deductive method, collection of bibliographic and documentary data, developed in order to make considerations about cyberculture, especially with regard to intellectual technological support capable of providing answers for the various areas of human knowledge, making it more accessible, transparent and economical. Finally, it is concluded in view of the results that artificial intelligence, does not manage to produce cognitive abilities of high intelligences to materialize the decision standard along the lines of human intelligence, however, one can think about its influence in the light of models of patronized information by algorithms.